Decreased Platelet Reactivity and Function in a Mouse Model of Human Pancreatic Cancer - Kawano, Tomohiro; Hisada, Yohei; Grover, Steven P.; Schug, Wyatt J.; Paul, David S.; Bergmeier, Wolfgang; Mackman, Nigel (Thrombosis and Haemostasis, 2023)
Cancer patients have increased thrombosis and bleeding compared with the general population. Cancer is associated with activation of both platelets and coagulation. Mouse models have been used to study the dysregulation of platelets and coagulation in cancer. We established a mouse model of pancreatic cancer in which tissue factor-expressing human pancreatic tumors (BxPC-3) are grown in nude mice. Tumor-bearing mice have an activated coagulation system and increased venous thrombosis compared to control mice. We also showed that tumor-derived, tissue factor-positive extracellular vesicles activated platelets ex vivo and in vivo. In this study, we determined the effect of tumors on a platelet-dependent arterial thrombosis model. Unexpectedly, we observed significantly reduced carotid artery thrombosis in tumor-bearing mice compared to controls. In addition, we observed significantly increased tail bleeding in tumor-bearing mice compared to controls. These results suggested that the presence of the tumor affected platelets. Indeed, tumor-bearing mice exhibited a significant decrease in platelet count and an increase in mean platelet volume and percentage of reticulated platelets, findings that are consistent with increased platelet turnover. Levels of the platelet activation marker platelet factor 4 were also increased in tumor-bearing mice. We also observed decreased platelet receptor expression in tumor-bearing mice and reduced levels of active αIIb/β3 integrin in response to PAR4 agonist peptide and convulxin in platelets from tumor-bearing mice compared with platelets from control mice. In summary, our study suggests that in tumor-bearing mice there is chronic platelet activation, leading to thrombocytopenia, decreased receptor expression, and impaired platelet adhesive function.
Keywords: bleeding; cancer; extracellular vesicles; platelet; thrombosis